One health. Expectations and demands of veterinary medicine - Villamil Jiménez, Luis C. (Revista Colombiana de Ciencias Pecuarias, 2019)
Health and disease, have been topics of interest in several cultures since the beginning of mankind. Those cultures, in their diversity, have tried to resolved and answer the several questions regarding outbreaks and epidemics in animal and human populations. The interpretations were as varied as the cultures that produced them: some thought they were secondary to divine punishments, spells or wizardry, others secondary to environmental forces. With globalization, the world was microbially unified, the exchange of goods and people also carried several diseases. Medical knowledge used several theories and remedies to understand and confront them. When medicine and veterinary sciences were formalized as a study field, sick individuals were protagonists and population health was put aside; animal and human interactions were secondary. This era, which is characterized by scarcity of resources, continuous increase in the population number and the requirements of food and water, as well as a climatic crisis, coincides with dramatic changes in the clinical presentation of diseases; some, are characteristically human others shared with animals; the emergence and re-emergence of neglected diseases, changes in the usual etiological agents (as well as the appearance of new pathogens, some originated from animals), have originated a crisis: the necessary services and diagnostic infrastructures are non-existent, there is an unavailability of vaccines or specific therapies and there are concerns regarding antimicrobial resistance. These aspects push for the development of new strategies and definitions. The world must be up to the sanitary challenges, adopting new focuses. In this regard, One Health can be an interdisciplinary and intersectoral sanitary strategy capable of aligning human talent from human and animal health sectors, as well as research and education institutions, which are important agents for public and animal health. This action would allow the conformation ideal teams to be able to face the multiples diseases in the XXI century. In this aspect veterinary medicine comes upfront.